Pemberdayaan Masyarakat dalam Mengenali Tanda-Tanda Bahaya pada Masa Kehamilan di Desa Penyengat Olak Kabupaten Muaro Jambi Tahun 2020 - Herinawati Herinawati; Diniyati Diniyati; Atika Fadhilah Danaz; Iksaruddin Iksaruddin (Jurnal Abdimas Kesehatan (JAK), 2021)
According to a report from the World Health Organization (WHO), maternal mortality generally occurs due to complications during and after pregnancy. As for the types of complications that cause the majority of maternal deaths, about 75% of the total maternal deaths are bleeding, infection, high blood pressure during pregnancy, complications of childbirth and unsafe abortion, these become very chronic considering the various causes of maternal death above are actually can be prevented by providing knowledge and understanding to pregnant women about the danger signs in pregnancy, if you experience that you immediately come to the health center or health personnel so that delays can be prevented, the mother immediately gets help which in turn can reduce cases of maternal death This activity aims to increase community empowerment in recognizing and preventing danger signs during pregnancy in Penyengat Olak Village, Muaro Jambi Regency in 2020. The targets are all pregnant women, husbands of pregnant women, community leaders, religious leaders and PKK mothers in Penyengat Olak Village. The method used is pre-test and post-test using a questionnaire, lectures and discussions. The speaker in this activity was a team of lecturers at the Poltekkes Ministry of Health Jambi, Department of Midwifery. The results of community service activities are the formation of community groups who are able to independently have knowledge and skills in recognizing danger signs during pregnancy in Penyengat Olak Village, Jambi Luar Kota District, Muaro Regency